PEMBERDAYAAN KARANG TARUNA DESA ASINAN MELALUI BUDIDAYA JAMUR MERANG MENGGUNAKAN ECENG GONDOK (EICHHORNIA CRASSIPES) RAWA PENING - Andari Puji Astuti; Eko Yuliyanto; Agustin Rahmawati (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
The abundant natural potency in Asinan village is water hyacinth, but its processing is not yet optimal.IbM is aimed at empowering the Asinan village cadars to utilize the composting of hyacinth for mushroom cultivation. Mushrooms developed in the village of Asinan are mushroom. The reason for the cultivation of mushroom is because this mushroom can grow on water hyacinth substrate. In addition, mushroom also has a large market share while the availability of mushroom stocks are still very limited. The method of the implementation of community service activities to the Asinan village youth cultivators through the cultivation of mushrooms using water hyacinth as a growth medium in detail described in the following stages: 1.Socialization of community service activities about the potential development of Asinan village, Counseling and development of youth, giving mushroom cultivation materials merang, comparative study to mushroom village in yogyakarta, Practice of mushroom cultivation in village of Asinan.Hasil first harvest kumbung oneon 23 November 2016 got 8 kg mushroom. the next stage of post-harvest and post-harvest care for a community around the world and some of the World Bank's competitors. Keywords: Eceng gondok, mushroom, reef yam,